Master track of Eugen Seibold cruise ES22C04, Playa Blanca - Playa Blanca, 2022-03-09 - 2022-03-09 - Walter, David; Slagter, Hans A; Aardema, Hedy M; Calleja, Maria Ll; Heins, Lena; Hrabe de Angelis, Isabella; Weber, Jens; Dragoneas, Antonis; Pöhlker, Christopher; Schiebel, Ralf (Max Planck Institute for Chemistry, 2026)
This dataset contains the validated master track of the S/Y Eugen Seibold during expedition ES22C04, with a time resolution of about 10 seconds. This master track can be used as reference for further expedition data. For creating the master track, the 1-second resolution raw data acquired by the GPS position sensor on board S/Y Eugen Seibold were processed, averaging latitude and longitude within equidistant 10-second intervals. Quality control was performed visually and by checking the maximum speed calculated between neighbouring positions. In case of unrealistically high speeds, data points have been removed.